A robust, gravure-printed, silver nanowire/metal oxide hybrid electrode for high-throughput patterned transparent conductors. Issue 15 (22nd March 2016) - Scheideler, William J.; Smith, Jeremy; Deckman, Igal; Chung, Seungjun; Arias, Ana Claudia; Subramanian, Vivek
Abstract : We developed robust, gravure-printed, transparent conductors based on silver nanowires embedded in an indium zinc oxide matrix. Abstract : High-throughput patterning and enhanced mechanical stability are key to enabling large-area applications of metal nanowire mesh transparent electrodes. In this work, hybrid transparent conductors based on silver nanowires embedded in an indium zinc oxide matrix were prepared by high-speed gravure-printing (1.0 m s −1 ) from a single, stable liquid precursor. These gravure-printed films demonstrate excellent conductivity (9.3 Ω □ −1 ) and transparency ( T 550nm ∼ 91%), as well as robust mechanical properties. The encapsulating indium zinc oxide matrix dramatically improves adhesion, surface roughness ( R q < 5 nm), film uniformity, and thermal stability (up to 350 °C) of the embedded silver nanowires. These properties of the hybrid films make them a suitable electrode material for a variety of printed electronic devices, such as flexible OLEDs and solar cells.